Efek Program Pendampingan UMKM terhadap Performa Ketahanan Pendapatan dan Penyerapan Tenaga Kerja UMKM : Studi kasus Program JakPreneur DKI Jakarta - Fadhila, Farah Khoirur; Hanri, Muhammad (UI Scholars Hub, 2025)
This study discusses the effects of assistance program with business digitalization features, on the income resilience and labor absorption of the assisted MSMEs, case study of DKI Jakarta’s JakPreneur Program. Observation data from 2017-2021 tested business resilience under time and economic crisis challenge, cause of pandemic. Treatment group is 31 respondents of JakPreneur members who had participated since 2017 or 2018. Control group is SAKERNAS data from 2017-2021. The result shows that treatment groups had lower incomes but were able to retain workers compared to control groups. Their low income is due to limitations in implementing business digitalization and accounting.